O desvio no cinema de Guy Debord - Mota, César Carlos (2024)
The European avant-gardes marked the 20th century with their desire to reformulate art and transform the world through experimentation with language and political action. Heir to the Dadaists and Surrealists, the Situationist International was the group that, bringing together art and politics, took the desire for transformation to its ultimate consequences, culminating in its decisive influence on the May 68 uprising in France. This research deals with deviation (Détournement), a communication technique that synthesizes Situationist theory and practice. It is a form of parody which, by seizing the signs of a discourse, turns them against it. As part of the research, we studied this device in the cinema of Guy Debord, founder and one of the main representatives of the Situationist International. The aim is to locate the importance of deviation in his cinematographic work, how it manifests itself, what its relationship is with editing and its mechanisms for constructing meaning. We chose as our corpus one of the six films that Debord made: "The Society of the Spectacle". The methodology consists of bibliographical research that contextualizes and defines the deviation by its presuppositions and the theories that underpin it. The semiotics of Peirce and Greimas will be discussed and articulated so that they can serve as an analytical tool and a backdrop for understanding the problems involved in the construction of meaning. Only then will we move on to deal with the deviation in Guy Debord's film, seeking to answer the questions posed by the film.